2022
DOI: 10.1007/s12035-021-02686-2
|View full text |Cite
|
Sign up to set email alerts
|

piRNA/PIWI Protein Complex as a Potential Biomarker in Sporadic Amyotrophic Lateral Sclerosis

Abstract: The pathological hallmark of the majority of amyotrophic lateral sclerosis (ALS) cases is the mislocalization and aggregation of TAR DNA-binding protein 43 (TDP-43), an RNA-binding protein. Several studies have attributed disease processes of ALS to abnormal RNA metabolism. However, dysregulated biogenesis of RNA, especially non-coding RNA (ncRNA), is poorly understood. To resolve it, RNA-Seq, biochemical, and immunohistochemical analyses were performed on the pyramidal tract of the medulla oblongata of sporad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Nevertheless, the genetic background of ALS is still quite obscure, because the heritability of sporadic patients is estimated to be as high as 50% [ 4 ]. Accordingly, the contribution of long non-coding DNA and RNA is linked to the ALS disease process [ 5 , 6 , 7 ], and this is how, for example, the dysregulation of piRNA/PIWI proteins could have a role in ALS pathogenesis [ 8 ]. The majority of the genes associated with ALS are either susceptibility factors or genes linked to other neurodegenerative conditions; hence, they have no direct causal relationship with ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the genetic background of ALS is still quite obscure, because the heritability of sporadic patients is estimated to be as high as 50% [ 4 ]. Accordingly, the contribution of long non-coding DNA and RNA is linked to the ALS disease process [ 5 , 6 , 7 ], and this is how, for example, the dysregulation of piRNA/PIWI proteins could have a role in ALS pathogenesis [ 8 ]. The majority of the genes associated with ALS are either susceptibility factors or genes linked to other neurodegenerative conditions; hence, they have no direct causal relationship with ALS.…”
Section: Introductionmentioning
confidence: 99%
“…In human brains with sporadic ALS, three piRNAs, hsa-piR-000578 , hsa-piR-020871 , and hsa-piR-022184 , were upregulated, whereas two piRNAs, hsa-piR-009294 and hsa-piR-016735 , were downregulated ( Abdelhamid et al, 2022 ; Table 1 ). The expression level of HIWI/PIWIL1 was also increased in sporadic ALS brain tissues, whereas that of HIWI2/PIWIL4 was decreased ( Abdelhamid et al, 2022 ).…”
Section: Pirna and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In human brains with sporadic ALS, three piRNAs, hsa-piR-000578 , hsa-piR-020871 , and hsa-piR-022184 , were upregulated, whereas two piRNAs, hsa-piR-009294 and hsa-piR-016735 , were downregulated ( Abdelhamid et al, 2022 ; Table 1 ). The expression level of HIWI/PIWIL1 was also increased in sporadic ALS brain tissues, whereas that of HIWI2/PIWIL4 was decreased ( Abdelhamid et al, 2022 ). Furthermore, HIWI/PIWIL1 proteins were co-localized with TDP-43 in the motor neurons of sporadic ALS lumbar cords, suggesting that HIWI/PIWIL1 may contribute to the formation of TDP-43 inclusions ( Abdelhamid et al, 2022 ).…”
Section: Pirna and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has implicated the crucial role of PIWIL1 in neuronal development and protection in the migration of microtubules [ 355 ]. This observation suggested that PIWIL1 expression change can act as a compensatory mechanism for axonal dysfunction [ 356 ].…”
Section: Biosynthesis and Basic Functions Of Pirnasmentioning
confidence: 99%